Relationship between awareness of cervical cancer and HPV infection and attitudes towards HPV vaccine among women aged 15-49 years: a cross-sectional study - Engin Yurtçu; Reyhan Aydın Doğan; Büşra Karaaslan; Sibel Mutlu (São Paulo Medical Journal, 2022)
ABSTRACT BACKGROUND: Cervical cancer is a type of cancer caused by human papillomavirus (HPV). OBJECTIVE: To determine the relationship between awareness of cervical cancer and HPV infection and attitudes towards HPV vaccine among women aged 15-49 years. DESIGN AND SETTING: Cross-sectional study conducted at Karabük Training and Research Hospital, Turkey. METHODS: 500 women who visited the gynecology outpatient clinic of a public hospital between July 15 and December 31, 2019, were selected through random sampling. Data were collected using a sociodemographic questionnaire comprising nine questions (created by the researchers), the HPV and Cervical Cancer Awareness Questionnaire and the Carolina HPV Immunization Attitudes and Beliefs Scale. RESULTS: The relationship between the awareness questionnaire and the beliefs scale was explained through simple effect modeling of a structural equation. The women’s knowledge score regarding cervical cancer and HPV infection was 4.69 ± 4.02 out of 15. Women were afraid of being diagnosed with cervical cancer and HPV infection, but they did not have sufficient information. They had poor information about the HPV vaccine, did not know how to obtain the vaccine and did not have enough information about its benefits and harmful effects. Women who were afraid of getting cervical cancer, and who thought that they were at risk, had more information about the HPV vaccine. CONCLUSION: Women need information about cervical cancer, HPV infection and the HPV vaccine. Midwives, nurses and physicians who provide healthcare services in gynecological follow-ups should provide information to women about the HPV vaccine and cervical cancer.